Toxicity Of Fenvalerate On Larvae Of The Susceptible And Resistant Strains Of Tribolium Castaneum (Herbst) - Faruki, Saiful Islam; Yeasmin, Rogena; Das, Dipali Rani (Journal of Life and Earth Science, 2012)
Five-day old larvae of the susceptible (FSS-II) and organophosphorus-resistant (PH-I) strains of the red flour beetle Tribolium castaneum were exposed under laboratory conditions to food treated with 100, 250, 500 and 1000 ppm of a synthetic pyrethroid Fenvalerate up to adult emergence. The larval mortality was assessed at 1-, 3-, 7- and 15-days post-exposure, and up to pupation. PH-I was found less susceptible to Fenvalerate than FSS-II which required 1.2 to 3.1 fold more insecticide to induce 50% mortality. The pyrethroid treatments significantly increased the larval and pupal periods (P<0⋅05) in both the strains and the formation of pupal and adult progenies was adversely affected (P<0⋅001). DOI: http://dx.doi.org/10.3329/jles.v6i0.9717 JLES 2011 6: 27-31